Introduction: Accelerating policy progress in uncertain times - Resnick, Danielle; Diao, Xinshen; Tadesse, Getaw (International Food Policy Research Institute, 2020)
African agriculture is at an important crossroads. On the one hand, the role of agriculture in the process of economic transformation is widely recognized (Diao, Hazell, and Thurlow 2010; Diao and McMillan 2018), and there have been important achievements in African agricultural performance and productivity growth in recent years. For instance, between 2005 and 2012, agricultural value-added growth and total factor productivity growth were robust and positive for many countries in the region (IFAD 2016). Although more progress is still needed, long-standing structural reforms have contributed to a more conducive environment for private sector participation in African agriculture, particularly in input value chains (AGRA 2019). At the same time, governments are experimenting with a variety of policy interventions to accelerate agricultural transformation, including the creation of agro-industrial parks, agro-corridors, and special economic zones in more than two dozen countries across the continent (Gálvez Nogales and Webber 2017). These initiatives aim to create economies of scale by coordinating investments in transport, communications, power, and storage to foster linkages between farmers and agribusiness enterprises. There is enormous potential for these and other initiatives to enable agriculture to contribute to larger agrifood system transformation; in fact, evidence suggests that African agribusiness, inclusive of all aspects of the agrifood system except on-farm production, could be a US$1 trillion market by 2030 (Byerlee et al. 2013).